Low‐power dual‐band voltage‐controlled oscillator using a fourth‐order resonant technique. Issue 1 (4th October 2021) - Chang, Yu‐Hsin; He, Sih‐Sian
Abstract: A low‐power dual‐band voltage‐controlled oscillator (VCO) using a fourth‐order resonant technique implemented in 0.18‐μm CMOS process is presented in this letter. By utilizing a fourth‐order LC‐type resonant network and a current‐reused technique, the proposed VCO operates in the dual‐band mode and improves the overall performance. The tuning ranges of band 1 and band 2 are from 3.39 to 3.68 GHz and from 7.2 to 7.57 GHz controlled by a controlled‐voltage V C, respectively. The measured phase noises at 1 MHz frequency offset are −117.39 dBc/Hz and −113.58 dBc/Hz for output frequencies of 3.68 and 7.21 GHz, respectively. Besides, the figures‐of‐merit (FOM) at 3.68 and 7.21 GHz output frequencies are −182.5 and −184.5 dBc/Hz, respectively. The proposed VCO core consumes 4.2 mW from a 1.2‐V supply.